Effect of cross-sectional area of Reinforcement on Ultimate Shear Strength of RC Deep Beams - Farooq Mustafa, Al-Obaidi (2016)
The behavior of RC deep beams in shear failure is different from convention beams, and consequently, the design methods and analysis of these beams are different. Strut-and-tie Model (STM) is used to model the compression flow within the concrete strut. A series of simply supported deep beam were analyzed to seek how the shear span-to effective-depth ratio (a/d), transverse reinforcement, longitudinal reinforcement as well as the size of cross-sectional reinforcement affect the ultimate shear strength of reinforced concrete deep beam. A Free licensed software called "CAST" is used to draw and analyze the (STM) of RC deep beam. Based on the results, when the shear span-to-effective-depth ratio (a/d) increase, the ultimate shear strength decreases; and observed that increasing in concrete strength effect more on the ultimate shear strength when (a/d>1) compare to (a/d < 1) which has a lesser effect. Furthermore , and increment in the ultimate shear strength occurs when the amount of reinforcement, bar designation and the number of bars are increasing. However, shear strength ratio slightly decreases for (a/d < 0.5) and this is due to large effective transverse compression. The results obtained that by increasing the amount of shear reinforcement after a certain level, the shear strength of deep beam will be ineffective , and when the transverse reinforcement ratio exceeds a certain value, the ultimate shear strength of RC deep beams does not increase.